2019
DOI: 10.1128/msphere.00327-19
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Metabolism by Dendritic Cells Triggers an Antimicrobial Response against Mycobacterium tuberculosis

Abstract: Epidemiological evidence correlates low serum vitamin A (retinol) levels with increased susceptibility to active tuberculosis (TB); however, retinol is biologically inactive and must be converted into its bioactive form, all-trans retinoic acid (ATRA). Given that ATRA triggers a Niemann-Pick type C2 (NPC2)-dependent antimicrobial response against Mycobacterium tuberculosis, we investigated the mechanism by which the immune system converts retinol into ATRA at the site of infection. We demonstrate that granuloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Dehydrogenase/family member 9 (DHRS9) is a member of the short chain dehydrogenase/ reductase family [62]. Studies have shown that DHRS9 is involved in the biosynthesis of all trans-retinoic acid and exerts an anti-tumour role by inhibiting the proliferation of tumour cells, including acute promyelocytic leukemia, squamous cell carcinoma, neurocytoma and hepatocellular carcinoma [63][64][65]. The formyl peptide receptor 1 (FPR1), a G-protein-coupled receptor expressed by bone marrow-derived cells [66], participates in activation of immune cell induced by N-formyl peptide [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Dehydrogenase/family member 9 (DHRS9) is a member of the short chain dehydrogenase/ reductase family [62]. Studies have shown that DHRS9 is involved in the biosynthesis of all trans-retinoic acid and exerts an anti-tumour role by inhibiting the proliferation of tumour cells, including acute promyelocytic leukemia, squamous cell carcinoma, neurocytoma and hepatocellular carcinoma [63][64][65]. The formyl peptide receptor 1 (FPR1), a G-protein-coupled receptor expressed by bone marrow-derived cells [66], participates in activation of immune cell induced by N-formyl peptide [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells express dhrs9, although reports disagree as to the specific cells involved. One report concluded that macrophages do not express dhrs9, whereas granulocyte-macrophage colonystimulating factor-derived dendritic cells do (Kim et al, 2019). Dendritic cells would secrete ATRA to resist pathogenesis in M. tuberculosis-infected macrophages.…”
Section: Dhrs9 Contributions To Atra Biosynthesismentioning
confidence: 99%
“…The latter may explain frequent association of Raldh1 with cancer progression, not its ability to generate ATRA in some loci. In contrast, Raldh2 contributes to ATRA biosynthesis to trigger an antimicrobial response in tuberculosis: low expression of Raldh2 in lung characterizes the disease (Kim et al, 2019). ATRA has hormesis effects.…”
Section: Raldh and Diseasementioning
confidence: 99%
“…Although it is well known that nutritional deficiencies need to be diminished for the immune system to function adequately, recently emerged evidence suggest that increased intake of some nutrients, including vitamins, may help optimize the immune response and resistance to infection [6][7][8]. The impact of vitamin supplementation on the modulation of the immune response has always been in the focus of numerous studies [9][10][11][12]. We focused this review on vitamins A and D, since they were shown to have the greatest immunomodulatory impact.…”
Section: Introductionmentioning
confidence: 99%